Human and mouse essentiality screens as a resource for disease gene discovery - Cacheiro, Pilar; Muñoz-Fuentes, Violeta; Murray, Stephen A; Dickinson, Mary E; Bucan, Maja; Nutter, Lauryl M J; Peterson, Kevin A; Haselimashhadi, Hamed; Flenniken, Ann M; Morgan, Hugh; Westerberg, Henrik; Konopka, Tomasz; et al. (Nature communications, 2020)
The identification of causal variants in sequencing studies remains a considerable challenge that can be partially addressed by new gene-specific knowledge. Here, we integrate measures of how essential a gene is to supporting life, as inferred from viability and phenotyping screens performed on knockout mice by the International Mouse Phenotyping Consortium and essentiality screens carried out on human cell lines. We propose a cross-species gene classification across the Full Spectrum of Intolerance to Loss-of-function (FUSIL) and demonstrate that genes in five mutually exclusive FUSIL categories have differing biological properties. Most notably, Mendelian disease genes, particularly those associated with developmental disorders, are highly overrepresented among genes non-essential for cell survival but required for organism development. After screening developmental disorder cases from three independent disease sequencing consortia, we identify potentially pathogenic variants in genes not previously associated with rare diseases. We therefore propose FUSIL as an efficient approach for disease gene discovery.
Keywords: esenciální geny; Genes, Essential; Mice; myši knockoutované; nemoc; genomika; Animals; Disease; Humans; Genetic Association Studies; lidé; Genomics; genetické asociační studie; zvířata; Mice, Knockout; myši